A case report: Amplatzer occluder device closure of an iatrogenic ventricular septal defect following radiofrequency ablation. Issue 4 (12th April 2021) - Michaelis, Anna; Dähnert, Ingo; Riede, Frank-Thomas; Paetsch, Ingo; Jahnke, Cosima; Paech, Christian
Abstract: Background: Interventricular septal perforation is an extremely rare complication of radiofrequency ablation (RFA), with an incidence of 1%. The most common mechanism is a 'steam pop', which can be described as 'mini-explosions' of gas bubbles. Data for percutaneous repair of cardiac perforations due to RFA are limited. Case summary: A 78-year-old female patient was referred to our department for the treatment of two iatrogenic ventricular septal defects (VSDs) following radiofrequency ablation (RFA) of premature ventricular contractions. One week post-ablation, chest pain and progressive dyspnoea occurred. Transthoracic echocardiography detected a VSD, diameter 10 mm. Hence, iatrogenic, RFA-related myocardial injury was considered the most likely cause of VSD, and the patient was referred to our tertiary care centre for surgical repair. Cardiovascular magnetic resonance (CMR) imaging demonstrated border-zone oedema of the VSD only and confirmed the absence of necrotic tissue boundaries, and the patient was deemed suitable for percutaneous device closure. Laevocardiography identified an additional, smaller muscular defect that cannot be explained by analysing the Carto-Map. Both defects could be successfully closed percutaneously using two Amplatzer VSD occluder devices. Discussion: In conclusion, this case demonstrates a successful percutaneous closure of a VSD resulting from RFA using an Amplatzer septal occluder device. CMR might improve tissue characterization of the VSD borders and support the decision if to opt for interventional or surgical closure.